(3eYLe eG GSJYLes - (3YHO Gddg Hf YHO GdYRjR Hf eMeO GdHcQj GdCfOdSj, CHh YHjO,J (B487 (3g` s
(3ChdgG (B:s
(3GdMeO ddg MeOG JbJVi QVGg gPG cJGH hGdCNHGQ hGdJhGQjN s
(3BNQgG (B:s
(3jfJgi HGH GdMGA eY GdjGA (B( (3GdMjGA (B) s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B98 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B75s
(3eUOQ GbJfGA GdCUd (B:s
(3ef GdNRGfI GdYGeI HeOjfI GdQHGW (B(339) s
Keywords: (3GdLZQGajG h GdHdOGfs